Advanced Rietveld refinement and SEM analysis of tobermorite in chemically diverse autoclaved aerated concrete. Issue 2 (June 2019) - Schreiner, J.; Goetz-Neunhoeffer, F.; Neubauer, J.; Volkmann, S.; Bergold, S.; Webler, R.; Jansen, D.
Abstract : Changes of structural properties of tobermorite in autoclaved aerated concrete (AAC) for various compositions were characterized and the disadvantages of SEM analysis in this context are discussed. The influence of variations in the chemical composition of raw materials on lattice parameters, morphology and domain sizes of tobermorite was investigated by XRD and for comparison by SEM analysis. Particularly the effect of substitution by Al 3+ and (SO4 ) 2− in tobermorite structure was examined. The dimensions of coherently scattering domains were calculated based on the refinement of anisotropic peak broadening of tobermorite in XRD diffractograms using a Rietveld compatible approach. No effect of (SO4 ) 2− on the domain sizes and lattice parameters of tobermorite could be observed. The amount of anhydrite detected by quantitative XRD analysis indicates that all of the available (SO4 ) 2− is present as anhydrite. Lath-like shapes of domains and a larger c parameter are calculated whenever Al 3+ is incorporated in a considerable amount. Formation of katoite can be observed very clearly in SEM micrographs whenever the amount of available Al 3+ exceeds a distinct value in the dry mix. The effect of Al 3+ and (SO4 ) 2− on tobermorite morphology could not be observed clearly by SEM analysis in AAC samples.